Values of Akhlak Education Based on Suluk Tareeqa Naqsyabandiyah Kholidiyah - Setyo Pambudi; Ahmad Wahyu Hidayat (Program Studi Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2020)
This study raises the theme of the values ​​of Moral-Based Moral Education in the Naqsyabandiyah Kholidiyah Islamic Boarding School of Al-Manshur Popongan Klaten. The research method used is qualitative method, using the one used is phenomenology, the subject is the Murshid of the Naqshabandiyah Khalidiyah Order, the Naqshyabandiyah Khalidiyah Congregation and religious figures around the popongan Islamic boarding school, analyzing the data using structured analysis methods, monitoring, and triangulation of data. The results of his research are: 1) Moral Education in the Procession of Suluk Tarekat Naqsyabandiyah Kholidiyah Boarding School Al-Manshur Popongan Klaten. Based on the content of the requirements and the harmony of the above, that in the procession of suluk it takes the values ​​of moral education that is able to improve the quality of human beings to be perfect beings. And in it there are morals towards Allah SWT, Teachers, Students and Fellow. The implementation of suluk can also be actualized in social life, 2) Values ​​of moral education in the Suluk Naqsyabandiyah Kholidiyah pesantren Al-Mansur Boarding School in Klongan. That contains moral education which includes: 1. Morals towards God, namely Repentance, Gratitude, Tawakal, and Ikhlas. 2. Morals towards Teachers, namely Ridho, Ta'dzim, Obedience and Amanah. 3. Morals towards Yourself, namely Sidiq, Mujahadah, Istiqomah and Wara '. 4. Morals towards Others, C) Implementation of Suluk Naqsyabandiyah Kholidiyah in Community or Daily Life. 1. Ukhuwah Islamiyah, 2. Tawadhu ’, 3. Ta'awun and 4. Husnudzan